2008
DOI: 10.1074/jbc.m709051200
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan-CD44-ERK1/2 Regulate Human Aortic Smooth Muscle Cell Motility during Aging

Abstract: The glycosaminoglycan hyaluronan (HA) modulates cell proliferation and migration, and it is involved in several human vascular pathologies including atherosclerosis and vascular restenosis. During intima layer thickening, HA increases dramatically in the neointima extracellular matrix. Aging is one of the major risk factors for the insurgence of vascular diseases, in which smooth muscle cells (SMCs) play a role by determining neointima formation through their migration and proliferation. Therefore, we establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 55 publications
1
68
0
1
Order By: Relevance
“…We demonstrated previously that human aortic SMC (AoSMC) migration is strictly dependent on HA-CD44 signaling and recently reported that the HA synthesis inhibitor 4-methylumbelliferone (4-MU) reduced proatherosclerotic properties of AoSMCs by decreasing cell migration and proliferation and by inhibiting monocyte binding to the HA-rich ECM that contributes to inflammation (9,10). Moreover, we found that the simultaneous addition of HMW-HA to 4-MUtreated AoSMCs restored cell proliferation to the levels of controls.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…We demonstrated previously that human aortic SMC (AoSMC) migration is strictly dependent on HA-CD44 signaling and recently reported that the HA synthesis inhibitor 4-methylumbelliferone (4-MU) reduced proatherosclerotic properties of AoSMCs by decreasing cell migration and proliferation and by inhibiting monocyte binding to the HA-rich ECM that contributes to inflammation (9,10). Moreover, we found that the simultaneous addition of HMW-HA to 4-MUtreated AoSMCs restored cell proliferation to the levels of controls.…”
mentioning
confidence: 59%
“…collagen, fibronectin, laminin, HA, DS, and CS) (39,40), such CD44 isoforms could be involved in receptor-ligand recognition, thereby explaining the evidence that other GAGs as CS and DS inhibited the 4-MU-induced apoptosis. To test this hypothesis, we inhibited the HA-CD44 interaction by using the CD44-blocking Hermes-1 or BRIC235 monoclonal antibodies and by attenuating HA-CD44 signaling with a 34-mer HA oligosaccharide as we previously showed in AoSMCs (10). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, SMCs are responsible for HA matrix deposition after vessel injury, and HA itself can modulate SMC motility (11) and dedifferentiation (12). Several experiments confirmed the critical pro-atherosclerotic role of HA using CD44 knock-out animals (12) or HAS2 transgenic mice (13), by blocking HA/CD44 interaction (14), or by inhibiting HA synthesis (15).…”
Section: Protein It Is Composed Of Glcua and N-acetyl-d-glucosaminementioning
confidence: 77%
“…The following human TaqMan gene expression assays were used: HAS1 (Hs00155410_m1), HAS2 (Hs00193435_m1), HAS3 (Hs00193436_m1), UDP-glucose dehydrogenase (Hs00163365_m1), UDP-glucose pyrophosphorylase (Hs00198879_m1), and ␤-actin (Hs99999903_m1). The relative gene expression was determined by comparing ⌬C t (14).…”
Section: Methodsmentioning
confidence: 99%
“…They were processed using a biotinylated HA-binding protein and a green fluorescent reporter as described previously (20).…”
Section: Methodsmentioning
confidence: 99%